WIRELESS INDUCTIVE POWER TRANSFER, ORIENTED MODELING AND DESIGN - Jorgetto, Marcus F. C.; Melo, Guilherme de A. e [UNESP]; Canesin, Carlos A. [UNESP]; IEEE (Ieee, 2015)
This paper proposes a modeling, design methodology and shows the main simulation results to the development of a Wireless Power Transmission (WPT) element, applied to pure Electric Vehicles (EV). The proposed structure is composed of at least two inductors, composing a transmitter and an energy receiver with weak magnetic coupling among them, considering a far-field energy-transfer method. The modeling derived from inductors with cylindrical spiral shape, were analyzed using the Biot-Savart Law and the Third Maxwell Law of the electromagnetism. Through the use of Comsol (R) software were confirmed the theoretical results from the proposed modeling, obtaining an optimal WPT element for a small EV admitted as a case study. Furthermore, an important contribution presented in this paper is the analysis of arrangements for the inductive elements of power transmitter, presenting its advantages and disadvantages and the best configuration for the case study. Finally, it is informed that the experimental results from an implemented prototype, developed with the proposed methodology, will be presented in a future paper.
Keywords: Inductive Power Transfer; Wireless Power Transmission; Pure Electric Vehicles; Wireless Power Chargers